Temperature stress and redox homeostasis in agricultural crops - Awasthi, Rashmi; Bhandari, Kalpna; Nayyar, Harsh (Frontiers in Environmental Science, 2015)
Plants are exposed to a wide range of environmental conditions and one of the major forces that shape the structure and function of plants are temperature stresses, which include low and high temperature stresses and considered as major abiotic stresses for crop plants. Due to global climate change, temperature stress is becoming the major area of concern for the researchers worldwide. The reactions of plants to these stresses are complex and have devastating effects on plant metabolism, disrupting cellular homeostasis and uncoupling major physiological and biochemical processes. Temperature stresses disrupt photosynthesis and increase photorespiration altering the normal homeostasis of plant cells. The constancy of temperature, among different metabolic equilibria present in plant cells, depends to a certain extent on a homeostatically regulated ratio of redox components, which are present virtually in all plant cells. Several pathways, which are present in plant cells, enable correct equilibrium of the plant cellular redox state and balance fluctuations in plant cells caused by changes in environment due to stressful conditions. In temperature stresses, high temperature stress is considered to be one of the major abiotic stresses for restricting crop production. The responses of plants to heat stress vary with extent of temperature increase, its duration and the type of plant. On other hand, low temperature as major environmental factor often affects plant growth and crop productivity and leads to substantial crop loses. The present review discusses how oxidative damage as a result of temperature stress is detrimental for various crops. Various strategies adapted by the plants to main redox homeostasis are described along with use of exogenous application of some stress protectants.